The Implementation of Modified Traditional Engklek Game-Based Locomotor Learning to Improve Elementary School Students' Movement Skills - Rahmani; Perdinanto; Kuncoro Darumoyo; Muhammad Mulhim (Jurnal Master Penjas & Olahraga, 2026)
This study examined the effectiveness of locomotor learning (jumping) based on a modified traditional Engklek game in improving the movement skills of elementary school students at SDN Murung Sari 2 Amuntai. A quantitative approach with a one-group pretest–posttest design was employed. The participants were 48 second-grade students selected through total sampling. Data were collected using a locomotor movement skill assessment instrument based on established learning indicators and analyzed using descriptive statistics and paired-sample t-tests. The results demonstrated a significant improvement in students’ locomotor movement skills after the intervention, as reflected by higher posttest scores than pretest scores (p < 0.05). The modified Engklek game not only enhanced jumping performance but also improved balance, movement coordination, lower-limb strength, and active participation during physical education activities. Therefore, this learning approach can serve as an effective and engaging strategy for developing fundamental locomotor skills in elementary school students.